La práctica pedagógica y su incidencia en el contexto educativo - Rojas Rojas, Luz Miryan; Castillo Gutiérrez, María Consuelo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article aims to reflect on the pedagogical practice and its incidence in the educational context. Furthermore, from a theoretical review are contrasted different positions that arise from  the documentary exploration, to turn part from a reflection on this topic that is framed in the pedagogical endeavor, is it specifically addresses, in its definition and functionality, emphasizing  the role in the realities of the different contexts, models, training and experiences. Among the Conclusions we highlight the importance of the pedagogical practice that is based on the work, being articulated from the school, due to the teacher is essential in the educational community and its practice permeates the reality in the classroom.